2012
DOI: 10.3945/an.112.001974
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Physical Activity/Inactivity Factors Associated with Obesity in School-Aged Children

Abstract: Diet and physical activity (PA) are essential components of nutritional status. Adequate nutrition and an active lifestyle are key factors during childhood, because food habits track into adulthood. Children spend more time in school than in any other environment away from home. Studying the diet factors and patterns of PA that affect obesity risk in children during school hours and the complete school day can help identify opportunities to lower this risk. We directly measured the time children spent performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
13
2
4
Order By: Relevance
“…4,24 Although the Canadian Sedentary Behavior Guidelines recommend no more than 2 hours of screen time per day, 25 more than one-half of Mexican children and youth did not meet this recommendation. Several individual studies indicated that Mexican children 6-11 years spent, on average, 2.5-3 hours per day in front of a screen, [26][27][28] which was consistent with ENSANUT 2012 estimates. 4 Given the increase in prevalence of sedentary behavior (screen time), the grade for this indicator was reduced from 5 in the 2012 Report Card 9 to 4 in 2014.…”
Section: Sedentary Behavior: 4 (D)supporting
confidence: 62%
“…4,24 Although the Canadian Sedentary Behavior Guidelines recommend no more than 2 hours of screen time per day, 25 more than one-half of Mexican children and youth did not meet this recommendation. Several individual studies indicated that Mexican children 6-11 years spent, on average, 2.5-3 hours per day in front of a screen, [26][27][28] which was consistent with ENSANUT 2012 estimates. 4 Given the increase in prevalence of sedentary behavior (screen time), the grade for this indicator was reduced from 5 in the 2012 Report Card 9 to 4 in 2014.…”
Section: Sedentary Behavior: 4 (D)supporting
confidence: 62%
“…A infância é uma fase importante para a aquisição de comportamentos que poderão ser mantidos na vida adulta. 3,4 Diante disto, deve-se considerar que tal etapa se configura como um período sensível para a identificação de comportamentos nocivos à saúde, assim como o planejamento de abordagens voltadas à prevenção e controle destes comportamentos. 4,5 A prática habitual da AF apresenta-se como um importante componente para a manutenção da saúde 21 , fato corroborado pelos dados da Pesquisa Nacional de Saúde Escolar a qual apontou uma prevalên-cia de atividade física insuficiente entre crianças e jovens na ordem de 56,9%.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…3,4 Diante disto, deve-se considerar que tal etapa se configura como um período sensível para a identificação de comportamentos nocivos à saúde, assim como o planejamento de abordagens voltadas à prevenção e controle destes comportamentos. 4,5 A prática habitual da AF apresenta-se como um importante componente para a manutenção da saúde 21 , fato corroborado pelos dados da Pesquisa Nacional de Saúde Escolar a qual apontou uma prevalên-cia de atividade física insuficiente entre crianças e jovens na ordem de 56,9%. 22 Sendo assim, considerando o critério de classificação do risco relacionado à prática de AF adotado no presente estudo, observou-se que as meninas foram menos ativas, fator este, bem suportado pela literatura, o que pode ser explicado por características socioculturais, pois os meninos são mais estimulados à prática de atividade física em comparação às meninas.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
See 1 more Smart Citation
“…These obesogenic behaviours contribute to the prevalence of paediatric obesity. (19) Further, many children do not meet behavioural health recommendations. Approximately 30% of US 6-to 11-year-olds meet current PA guidelines of 60 min of moderate-to-vigorous PA per day.…”
Section: Introduction/rationale For Reviewmentioning
confidence: 99%